2016
DOI: 10.33762/bvetr.2016.124293
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Study on the Capacity of Biofilm Production in Staphylococcus Aureus Isolated From Bovine Subclinical Mastitis and Their Impact on Resistance to Antimicrobials

Abstract: The study was intended for identification and characterization of Staphylococcus aureus isolated from bovine subclinical mastitis cases. A total of 143 milk samples were collected from apparently normal cows from Basrah province. California mastitis test was used to detect 81 (56.6%) samples as subclinical mastitis. However, by using bacteriological and biochemical tests 36(44.44%) isolates were confirmed as S. aureus. Antimicrobials susceptibility assays of isolates revealed that, all of them were completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In recent years, MRSA has become a particularly significant problem in many regions on the world because of its ability to getting resistance to antimicrobial drugs (84), thus, the rapid recognition of MRSA was necessary for prompting effective treatment and preventing the dissemination of infection (85). Furthermore, the prevalence of MRSA differs considerably from one region to another and among farms in the same district, the data on the prevalence of MRSA in Iraq is limited, few studies were reported different prevalence rate in chickens, and slaughterhouses as follows: 61.1% and 53.8% (86,87), and 66.6%, 20.3%, and 27.3% among chickens and attached stations for slaughterhouses and poultry fields (42,88,89). Meanwhile, the prevalenve rate of MRSA in other countries was as follow 44% among chickens carcasses in Egypt (90), 9.5% among poultry meat in Jordan (91), in Algeria the prevalence of MRSA among broilers was 20%-50% according to (62,92) while in layer chickens in Egypt the prevalence was 60% (93).…”
Section: Identification Of Methicillin Resistance S Aureusmentioning
confidence: 99%
“…In recent years, MRSA has become a particularly significant problem in many regions on the world because of its ability to getting resistance to antimicrobial drugs (84), thus, the rapid recognition of MRSA was necessary for prompting effective treatment and preventing the dissemination of infection (85). Furthermore, the prevalence of MRSA differs considerably from one region to another and among farms in the same district, the data on the prevalence of MRSA in Iraq is limited, few studies were reported different prevalence rate in chickens, and slaughterhouses as follows: 61.1% and 53.8% (86,87), and 66.6%, 20.3%, and 27.3% among chickens and attached stations for slaughterhouses and poultry fields (42,88,89). Meanwhile, the prevalenve rate of MRSA in other countries was as follow 44% among chickens carcasses in Egypt (90), 9.5% among poultry meat in Jordan (91), in Algeria the prevalence of MRSA among broilers was 20%-50% according to (62,92) while in layer chickens in Egypt the prevalence was 60% (93).…”
Section: Identification Of Methicillin Resistance S Aureusmentioning
confidence: 99%